2007
DOI: 10.1002/jsfa.3068
|View full text |Cite
|
Sign up to set email alerts
|

Gelatine–starch films: Physicochemical properties and their application in extending the post‐harvest shelf life of avocado (Persea americana)

Abstract: BACKGROUND: Several storage techniques have been developed to extend the post-harvest shelf life of horticultural products. One method involves the use of edible or biodegradable coatings. Such coatings are made of biological materials that are used to coat fresh products, providing a semi-permeable barrier to water vapour and gases, e.g. O 2 and CO 2 . The influence of starch concentration, glycerol content and pH on the carbon dioxide permeability (CO 2 P) and mechanical properties of gelatine-starch edible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 32 publications
3
33
1
5
Order By: Relevance
“…During ripening, the green pigment chlorophyll degrades and carotenoids are synthesized [31] from colorless precursor (phytoene) to carotene (pale yellow), lycopene (red), -carotene (orange), xanthophylls, and hydroxylated carotenoids (yellow) [5,32] given the variation in the values of color parameters.…”
Section: 2mentioning
confidence: 99%
“…During ripening, the green pigment chlorophyll degrades and carotenoids are synthesized [31] from colorless precursor (phytoene) to carotene (pale yellow), lycopene (red), -carotene (orange), xanthophylls, and hydroxylated carotenoids (yellow) [5,32] given the variation in the values of color parameters.…”
Section: 2mentioning
confidence: 99%
“…There was only a small but not significant, respiration peak, on day 6 for the uncoated and kafirin-PG+GDL coated fruit and day 10 for kafirin-PG.. This lack of a clear maximum CO 2 production for "Hass" avocados was also described by Hershkovitz et al (2005) for control fruit and those treated with 1-Methylcyclopene and stored at 20 o C. Using hydrophilic coatings, methyl cellulose (Maftoonazad and Ramaswamy, 2005), pectin (Maftoonazad and Ramaswamy, 2008), and gelatin/starch (Aguillar et al, 2008), lower respiration rates were also recorded in coated "Hass" avocados when compared with controls.When comparing the effect of different coatings on the respiration rate of "Hass" avocados, hydrophobic coatings such as avocado wax, have been found to be more effective at lowering the rate of respiration than other coatings (Johnston and Banks, 1998). Differences in the respiration behavior of coated avocados can be attributed to the different gas exchange and water barrier characteristics of the coatings used (Johnston and Banks, 1998).…”
Section: Resultsmentioning
confidence: 80%
“…Avocado softening during ripening is attributed to degradation of cell wall components due to the activity of the enzymes, polygalacturonase, cellulase and pectin methylesterase (Joeng and Huber, 2004). It has been found that gelatinestarch based edible coatings lowered O 2 permeability and increased CO 2 retention and subsequently reduced the enzymic activity responsible for fruit softening (Aguillar-Méndez et al, 2008). It is probable that the kafirin coatings behaved in a similar way and that the somewhat lower respiration rate resulting from kafirin-PG+GDL was responsible for better retention of flesh firmness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the application of gelatine-starch coatings delayed the ripening process which resulted in firmer fruit and lower weight loss in "Hass". (188) In addition a delay in respiratory climacteric pattern by 3 days was noticed in coated fruits stored at 20 °C.…”
Section: Edible Coatingsmentioning
confidence: 97%